International journal of information systems for crisis response and management - IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2009)
The International Journal of Information Systems for Crisis Response and Management (IJISCRAM) is an academically rigorous outlet for research into crisis response and management. It is focused on the design, development, implementation, use and evaluation of IS technologies and methodologies to support crisis response and management. It explores issues critical to the application of IS to crisis response and management.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, no. 1 (Jan./Mar. 2009); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 2, no. 2 (Apr./June 2010).
Keywords: Crisis management -- Periodicals; Emergency management -- Periodicals; Communications in management -- Periodicals; Case studies; Research methods; Collaborative and intelligent systems; Command and control; Communication technologies; Crisis planning, training, exercising, and gaming; Data fusion, representation, and visualization; Decision making and judgment; Disaster risk reduction; Risk management; Sensor networks; Early warning systems; Emergency response systems; Geographical information systems; Globalization and development issues; Healthcare; Health information systems; Human-computer interaction; Humanitarian operations; Information systems strategy; Knowledge management and systems; Systems interoperability information systems infrastructures; Virtual teams and organizations; Electronic books